Aftereffects of Resisted Muscle Contractions on the Accuracy of Joint Position Sense in Elite Male Athletes - Stillmann, B. C.; McMeeken, J. M.; Macdonell, A. L. (Archives of Physical Medicine and Rehabilitation, 1998)
Objective: To examine the effects of quadriceps and hamstring muscle strength testing on the results of subsequent knee joint position sense tests. Design: A case-control study of 40 elite male athletes divided equally into two groups, experimental and control. Methods: Both groups underwent position sense tests of both knees, with eyes closed, with isometric maintenance of the knee in each test position, return of the limb to the starting position, then active replication of the perceived test position using the same limb. In the experimental group, joint sense testing commenced 5 to 25min after strength testing of quadriceps and hamstring muscle strength in both legs using maximum isokinetic contractions at plateau speeds of 60°/sec and 120°/sec. The control group did not undergo pretest muscle strength testing. Results: The difference in the mean absolute (signless) and relative (signed) position sense errors between the experimental and control groups was 0.8° and 1.4°, respectively. The difference between the standard deviation of the relative errors was 1.2°. These results were not statistically significant (analysis of variance p = .24, .12, and .13, respectively). Conclusion: In elite male athletes knee joint position sense is unaffected by nonfatiguing strength tests conducted 5 to 25min before position sense testing. In: Arch Phys Med Rehabil 1998;79:1250-1254